PSYCHOLOGICAL FACTORS INFLUENCING THE DEVELOPMENT OF PROFESSIONAL IDENTITY IN STUDENTS - Saidova Farogat Otabek kizi (Ethiopian International Journal of Multidisciplinary Research, 2026)
This article comprehensively analyzes the psychological factors that affect the development of professional identity in students. In particular, the motivational sphere of the individual, the level of self-awareness, professional interests, values, the influence of the social environment and reflection processes are considered as important determinants in the formation of professional identity. Modern research shows that a significant part of students of higher educational institutions is receiving education without fully understanding their professional direction, which can negatively affect their future work. According to international and national statistical data, a certain part of young people does not work in their specialty after graduation, which indicates that professional identity is not sufficiently formed. Also, the results of the study serve to identify the possibilities of developing professional identity in students through an in-depth study of psychological factors. The article analyzes the problem based on the combination of theoretical and practical approaches and develops proposals.